The Influence of Halal Labels and Electronic Word of Mouth (E-WOM) on Purchase Decisions of Food and Beverage Products on the Shopee Online Site - Rosyid, Muhammad Abdul; Zuana, Muhammad Mujtaba Mitra; Muawanah, Muawanah (Department of Sharia Economics Institut Pesantren KH. Abdul Chalim Mojokerto, 2023)
E-commerce is a new concept that can be used as a process of buying and selling goods or services. Shopee is one of the e-commerce companies whose users are increasing every year. The use of the Shopee application is in great demand through sharing circles, especially among students. In buying a product, halal labels and information about the product are very important with the existence of electronic word of mouth as an information medium usually a consideration for deciding to buy the product. The purpose of this study is to prove that there is an influence of halal labels and electronic words of mouth partially and simultaneously on purchasing decisions in students of the Faculty of Sharia. This type of research is quantitative research with the survey method. The data used in this study are primary data and also secondary data. Data collection is carried out using the questionnaire method. The number of populations in this study is not known exactly the number, the sample used in this study amounted to 82 respondents. The analysis technique used in this study is a multiple linear regression analysis technique. Halal labels and electronic word of mouth simultaneously have a positive and significant effect on purchasing decisions for food and beverage products on the Shopee online site. This is indicated by a calculated F value of 59.149 and a table F value of 3.11. The significance value is < 0.001. The value indicates that the calculated F value > F of the table and the significance value of the < 0.05.